Maternal Determinants of Stunting Among Children Under Five Years Old in Kamonyi District, Southern Rwanda - Gisubizo Fabien; Dushimimana Anicet; Amena Al-Dubai; Ramzy Alothmany (Media Publikasi Cendekia Indonesia, 2026)
Childhood stunting persists as a major public health concern in Rwanda, characterized by significant sub-national inequalities despite broader national improvements in health indicators. This research evaluated the impact of maternal characteristics on stunting among children under five in Kamonyi District. A cross-sectional design was utilized, assessing 420 mother-child pairs selected via two-stage cluster sampling. Child nutritional status was determined using WHO standard HAZ scores, while maternal socio-demographic and health data were gathered through structured questionnaires. Statistical analysis identified a 37.1% stunting rate in the study population. Key maternal predictors significantly associated with child stunting (p<0.05) included limited education, short physical stature (<150 cm), underweight status (BMI <18.5 kg/m²), and inadequate utilization of antenatal care (ANC) services. Conversely, maternal age and employment status were not statistically correlated. The study concludes that addressing structural barriers to maternal education, nutritional health, and ANC utilization is crucial in high-risk districts to interrupt the intergenerational transmission of undernutrition